Zn 2PÃ¢â€šÂ/Ã¢â€šâ€š and Zn 2PÃ¢â€šÆ’/Ã¢â€šâ€š Electron Binding Energies with Nitrogen in Chitosan-Zinc Acetate Membranes Determined by X-Ray Photoelectron Spectroscopy Studies - M.Z.A, Yahya; A.M.M, Ali; R, Puteh; R, Yahya; M.A, Yarmo M.A; A.K, Arof (Malaysian Journal of Science, 2002)
Chitosan and zinc acetate complexes were prepared by dissolving the polymer in different amount of salt and in 100 ml 1 % acetic acid solution and casting the solutions onto various petri dishes for film formation at room temperature. Complexation between the zinc cation and the nitrogen atom in the amine group of the chitosan can be proven by x-ray photoelectron spectroscopy (XPS). The peak at ~401 eV indicates N-Zn interaction. The peaks at ~1025 eV and ~1048 eV are attributable to the Zn 2p$_{3/2}$ and Zn 2P$_{1/2}$ electron binding energy with the nitrogen donor in chitosan